Finite and infinite singular arc in Chemotherapy schedulling using optimal control theory / Marziehalsadat Jazayeri Shooshtari - Marziehalsadat, Jazyeri Shooshtari (2018)
Cancer is one of the leading causes of death globally and chemotherapy being an effective approach for treatment has to be closely monitored and scheduled. In this work optimal control theory is used to schedule the administration of Temozolomide as a chemo drug. After obtaining the Hamiltonian function the cases of singular arcs are discussed. It is shown that the control of this treatment consists of both finite order and infinite order singular arcs. Finite order singular arcs in this work are of the third order and can be derived after deriving the switching function (